"IV plasty" a novel technique: Cystic duct flap closure following common bile duct exploration in children - Olugbenga Michael Aworanti; Anna Radford; Naved K. Alizai (Elsevier, 2022)
Choledocholithiasis is increasingly seen in children; attributable to ever increasing diagnostic ultrasound availability and to the advances in medical care, including parenteral nutrition for children who have survived neonatal short bowel syndrome. Endoscopic expertise for managing paediatric choledocholithiasis is often unavailable or the procedure unsuccessful. Many of these children have multiple comorbidities and may have had previous laparotomies. Open Common Bile Duct (CBD) exploration becomes necessary in a large percentage of such children. The size and anatomy of the biliary tree often precludes a trans-cystic approach to CBD exploration. For this reason, frequently a choledochotomy is required. To avoid CBD stricture, insertion of a T-tube or stent is recommended, but these are associated with complications and appropriate small size devices are often unavailable. We present a technique for closure of the CBD after a choledochotomy that prevents the duct from narrowing, without the use of stents. This technique can also be employed for other tubular structures.